Nano- and micro-scale zerovalent iron-activated peroxydisulfate for methyl phenyl sulfoxide probe transformation in aerobic water: Quantifying the relative roles of SO4·−, Fe(IV), and ·OH. (1st September 2022) - Wang, Zhen; Yu, Yangyi; Guo, Qin; Guan, Chaoting; Jiang, Jin
Highlights: Evolution of Fe(IV), SO4 ·−, and · OH in mZVI/PDS process shows three-stage behavior. Role of Fe(IV) relative to SO4 ·− increases in Stage I and plateaus in Stage II. Relative role of · OH formed by ZVI aerobic oxygenation takes the lead in Stage III. Initial promotion of the relative role of Fe(IV) in nZVI/PDS process is negligible. Effects of pH and reactant dose on reactive oxidant evolution are explored. Abstract: Multiple reactive intermediates have been proposed to be involved in peroxydisulfate (PDS) activation by zerovalent iron (ZVI), including sulfate radical (SO4 ·− ) produced via iron-oxide shell mediated electron transfer, ferryl ion species (Fe(IV)) formed from Fe(II)-PDS interaction, and hydroxyl radical ( · OH) generated by ZVI aerobic oxygenation. In this study, evolution of the relative role of these intermediates in microscale and nanoscale ZVI (mZVI vs. nZVI) activated PDS processes is comparatively investigated by using a methyl phenyl sulfoxide (PMSO) probe that selectively reacts with Fe(IV) to produce methyl phenyl sulfone (PMSO2 ). Interestingly, during PMSO transformation by mZVI/PDS process, yields of PMSO2 (η(PMSO2 )) exhibit three-stage behavior that they first increase to a maximum (∼80% but lower than 100%) (Stage I) and then plateau for a period (Stage II) followed by a decrease phase (Stage III). Accordingly, the relative role of Fe(IV) in PMSO transformation is unceasingly improved in Stage I and subsequently reaches equilibrium with that of free radicals in Stage II, while it finally decreases in Stage III. Similar η(PMSO2 ) evolution trends are obtained in nZVI/PDS process, except that the η(PMSO2 ) increase in Stage I is negligible, possibly due to the exceptional fast nZVI dissolution. It was further clarified by tert -butyl alcohol scavenging assay that, in addition to Fe(IV), the free radical involved in Stages I and II is SO4 ·−, while · OH was dominant in Stage III. Moreover, studies on O2 effect reveal that ZVI aerobic oxygenation participates in mZVI corrosion during the entire process, while it is only involved in nZVI corrosion when PDS content is reduced to a low concentration, indicating that the reactivities of PDS and O2 are similar in mZVI corrosion, but differ greatly in nZVI corrosion. Additionally, effects of reactant dose and pH on η(PMSO2 ) evolution are also explored. Dynamics of the relative role of different reactive oxidants should be taken into account in further applications of ZVI/PDS in situ chemical remediation technology considering their different chemistries. Graphical abstract: Image, graphical abstract